Modulation of physical properties of oxide thin films by multiple fields - 杨华礼 王保敏 朱小健 尚杰 陈斌 李润伟 (Chinese physics B, 2016)
Recent studies of the modulation of physical properties in oxide thin films by multiple fields are reviewed.Some of the key issues and prospects of this area of study are also addressed.Oxide thin films exhibit versatile physical properties such as magnetism,ferroelectricity,piezoelectricity,metal–insulator transition（MIT）,multiferroicity,colossal magnetoresistivity,switchable resistivity.More importantly,the exhibited multifunctionality can be tuned by various external fields,which has enabled demonstration of novel electronic devices.